Riesgos cardiovasculares en conductores profesionales de la Cooperativa de Transportes Espejo de la ciudad de "El Ángel" - Mena Cuaical, Lesly Eliana (2025)
The main objective of this research project was to develop preventive interventions for cardiovascular risks among professional drivers of the "Espejo" Transport Cooperative. To carry out this project, a cross-sectional quantitative methodology was used, which facilitated the collection of relevant data throughout the research. The study was conducted in a descriptive, field, and bibliographic manner, allowing for a closer analysis of cardiovascular risks. Theoretical methods such as analytical-synthetic, inductive-deductive, and historical logical approaches were applied, contributing to a deeper understanding of the problem. The population and sample consisted of 64 drivers from the "Espejo" Transport Cooperative, considering all drivers due to their small number. For data collection, a survey focused on cardiovascular risks was conducted. The results obtained were as follows: 67% of the drivers had a lack of knowledge about cardiovascular risks. Regarding the diagnosis of cardiovascular diseases, it was found that 41% suffered from hypertension, 30% from obesity, and 20% from diabetes. Additionally, 63% of the drivers reported smoking several times a week, averaging 3 to 4 days. Regarding physical activity, 95% did not exercise, representing a high risk of developing cardiovascular and metabolic diseases. On an emotional level, stress was identified as a factor affecting 92% of drivers due to long working hours and limited rest time. Based on these results, a proposal was developed, primarily focusing on intervention strategies related to education, health promotion, and disease prevention. Information on cardiovascular risks was provided, and healthy habits were encouraged to reduce risk factors among professional drivers.